Weight Regain in U.S. Adults Who Experienced Substantial Weight Loss, 1999–2002 - Weiss, Edward C.; Galuska, Deborah A.; Kettel Khan, Laura; Gillespie, Cathleen; Serdula, Mary K. (American journal of preventive medicine, 2007)
Relatively few studies have focused on who is at risk for weight regain after weight loss and how to prevent it. The objectives of this study were to determine the prevalence and predictors of weight regain in U.S. adults who had experienced substantial weight loss. Data were analyzed from the 1999–2002 National Health and Nutrition Examination Survey (NHANES). This study examined U.S. adults aged 20–84 years who were overweight or obese at their maximum weight (body mass index ≥25) and had experienced substantial weight loss (weighed 10% less than their maximum weight 1 year before they were surveyed) ( n=1310). Compared to their weight 1 year ago, 7.6% had continued to lose weight (>5%), 58.9% had maintained their weight (within 5%), and 33.5% had regained weight (>5%). Factors associated with weight regain (vs weight maintenance or loss) included Mexican American ethnicity (versus non-Hispanic white) (odds ratio [OR]=2.0; 95% confidence interval [CI]=1.3–3.1), losing a greater percentage of maximum weight (≥20% vs 10% to <15%) (OR=2.8; 95% CI=2.0–4.1), having fewer years since reaching maximum weight (2–5 years vs >10 years) (OR=2.1; 95% CI=1.2–3.7), reporting greater daily screen time (≥4 hours vs 0–1 hour) (OR=2.0; 95% CI=1.3–3.2), and attempting to control weight (OR=1.8; 95% CI=1.1–3.0). Finally, weight regain was higher in those who were sedentary (OR=1.8; 95% CI=1.0–3.0) or not meeting public health recommendations for physical activity (OR=2.0; 95% CI=1.2–3.5). How to achieve the skills necessary for long-term maintenance of weight loss in the context of an obesogenic environment remains a challenge.